Mepolizumab as the first targeted treatment for eosinophilic granulomatosis with polyangiitis: a review of current evidence and potential place in therapy - Faverio P; Bonaiti G; Bini F; Vaghi A; Pesci A (Dove Medical Press, 2018)
Paola Faverio,1,2 Giulia Bonaiti,1,2 Francesco Bini,3 Adriano Vaghi,3 Alberto Pesci1,2 1School of Medicine and Surgery, University of Milano-Bicocca, Monza, Italy; 2Respiratory Unit, San Gerardo Hospital, ASST di Monza, Monza, Italy; 3ASST-Rhodense, UOC Pneumologia, Garbagnate Milanese, Milan, Italy Abstract: Mepolizumab is an anti-interleukin-5 (IL-5) humanized monoclonal antibody that binds to free IL-5. It induces bone marrow eosinophil maturation arrest and decreases eosinophil progenitors and subsequent maturation in the blood and bronchial mucosa. Its use has been extensively studied in severe eosinophilic asthma at a dose of 100 mg subcutaneously (SC) every 4 weeks and, more recently, in other hypereosinophilic syndromes. Eosinophilic granulomatosis with polyangiitis (EGPA) is an eosinophilic vasculitis that may involve multiple organs. Characteristic clinical manifestations are asthma, sinusitis, transient pulmonary infiltrates and neuropathy. Among the numerous pathways involved in the pathogenesis of EGPA, the Th-2 phenotype has a main role, as suggested by the prominence of the asthmatic component, in triggering the release of key cytokines for the activation, maturation and survival of eosinophils. In particular, IL-5 is highly increased in active EGPA and its inhibition can represent a potential therapeutic target. In this scenario, mepolizumab may play a therapeutic role. After some positive preliminary observations on the use of mepolizumab in small case series of EGPA patients with refractory or relapsing disease despite standard of care treatment, a randomized controlled trial was published in 2017. Mepolizumab at a dose of 300 mg administered by SC injection every 4 weeks proved effective in prolonging the period of remission of the disease, allowing for reduced steroid use. The positive results of this study, which met both of the primary endpoints, led to the approval in the USA of mepolizumab in adult patients with EGPA by the Food and Drug Administration in 2017. Therefore, mepolizumab can be officially considered as an add-on therapy with steroid-sparing effect in cases of relapsing or refractory EGPA. However, the most appropriate dose and duration of therapy still need to be determined. Future studies on larger multinational populations with prolonged follow-up are warranted. Keywords: mepolizumab, eosinophilic granulomatosis with polyangiitis, Churg–Strauss syndrome